1996
DOI: 10.1109/61.489316
|View full text |Cite
|
Sign up to set email alerts
|

Development of 500-kV XLPE cables and accessories for long-distance underground transmission lines. IV. Electrical properties of 500-kV extrusion molded joints

Abstract: Joints for 500-kV XLPE cable are now under development inJapan to enable the long-distance transmission of high-capacity power to urban areas. Basic research was carried out from 1989 to 1992 that determined joint type and design values. This paper reports on the electric performance of the fabricated joints.Various tests were conducted to evaluate the performance and the design values. As a results of this evaluation it was found that it was possible to realize joints for 500-kV XLPE cable.Field tests will be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Power cable accessories are important part of the cable system [1] . It is found that the failure rate of cable accessories is much higher than that of cable body.…”
Section: Introductionmentioning
confidence: 99%
“…Power cable accessories are important part of the cable system [1] . It is found that the failure rate of cable accessories is much higher than that of cable body.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer dielectric composites for filling inorganic nanoparticles into low-density polyethylene (LDPE) can acquire a significant improvement in the dielectric performances of polyethylene insulation materials by inhibiting space charge accumulations and charge injections [ 10 , 11 , 12 , 13 , 14 ]. For Al 2 O 3 /LDPE nanocomposites, the internal space charge quantity is highly correlated with the nanofiller concentration, which approaches the minimum level at a filling content of 1.0 wt%, implying the optimal balance point of suppressing space charge accumulations with the nanofiller concentration [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The defects in the cable joint are the main cause of explosion accidents. Many studies have been conducted to investigate the electric field distribution and aging process of main cable body, whereas studies of the cable joint are inadequate due to its complicated structure and multiple installation procedures [9,10]. This paper focuses on the electric field analysis around the 10 kV cable joint to determine the characteristics of the field distribution corresponding to each typical defect.…”
Section: Introductionmentioning
confidence: 99%